Konseling Berhenti Merokok dan Grup Terapi Dapat Menurunkan Perilaku Merokok pada Remaja di Kecamatan Bogor Barat - Ni Putu Ariani; Ati Nuraeni (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2012)
Adolescence is a period of transition from childhood to adulthood.During this period, adolescents are at risk of smoking behavior problems.Problems also occurred in the city of Bogor.ln 2006, the number of students as smokersin West Bogor as much as 36.9 percent.ln 2008 the proportion had increased to 55 percent.This study aimed to know the difference of effectiveness between smoking cessation counseling and group therapy to the smoking behavior.This study used a quasi-experimental design with two treatment groups which were a group therapy group and individual smoking cessation counseling.Number of samples was 18 respondents in counseling group and 18 respondents in the therapy group. The results showed that in counseling group decline in the number of cigarettes smoked per day from an average of 6.11 to 3.50 cigarettes/day. In group therapy group there was also reduction in the number of cigarettes smoked per day from an average of 4.82 to 3.28 cigarettes/day. There was no difference between the effectiveness of smoking cessation counseling to group therapy. However, there was a significant effect of smoking cessation counseling and group therapy for adolescent smoking behavior.Thus, smoking cessation counseling and group therapy was effective to reduce smokingbehavior in adolescent.